2016
DOI: 10.1002/pd.4779
|View full text |Cite
|
Sign up to set email alerts
|

Adverse perinatal outcomes are more frequent in pregnancies with a low fetal fraction result on noninvasive prenatal testing

Abstract: Objective This study aimed to assess risk of an adverse perinatal outcome for women with a low fetal fraction (LFF) result on noninvasive prenatal testing (NIPT).Study Design A retrospective cohort study whereby women with an LFF result were compared with women who had a sufficient fetal fraction (SFF) result on NIPT. Inclusion criteria were singleton pregnancies with quantification of fetal fraction and pregnancy outcome information. Primary outcome was a composite of any of the following: miscarriage, fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 31 publications
5
64
1
4
Order By: Relevance
“…Because we observed 3/11 samples in the validation set that were excluded because of insufficient fetal DNA fraction to be abnormal (two trisomy 18 and one triploidy), we suggest paying extra attention to pregnancies revealing low SeqFF result. This observation is supported by a recent publication . We performed a simple yet powerful analysis for the determination of fetal sex.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Because we observed 3/11 samples in the validation set that were excluded because of insufficient fetal DNA fraction to be abnormal (two trisomy 18 and one triploidy), we suggest paying extra attention to pregnancies revealing low SeqFF result. This observation is supported by a recent publication . We performed a simple yet powerful analysis for the determination of fetal sex.…”
Section: Discussionsupporting
confidence: 74%
“…This observation is supported by a recent publication. 24 We performed a simple yet powerful analysis for the determination of fetal sex. The model correctly predicted the fetal sex of 172/173 samples of the validation set and gave an incorrect result for one triploid fetus (69,XXY).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there was no significant difference in fetal cfDNA levels in women who developed pre-eclampsia and women who did not develop pre-eclampsia in a recent nested case–control study 14. A retrospective cohort study on 348 women undergoing NIPT found a low fetal fraction in 22 (6%) women and an association between low fetal fraction and adverse perinatal outcome with an adjusted OR of 2.5 15. In the study, patients with low fetal fraction were more likely to have pregnancy-associated hypertensive disorders, including pre-eclampsia (59.1% compared to 26.4%, p=0.001).…”
Section: Discussionmentioning
confidence: 79%
“…In the study, patients with low fetal fraction were more likely to have pregnancy-associated hypertensive disorders, including pre-eclampsia (59.1% compared to 26.4%, p=0.001). Other significant adverse perinatal outcomes included preterm birth <37 weeks of gestation 15. There was no mention if patients with poor outcomes had associated autoimmune disorders or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Here the test is repeated to exclude technical problems with another 10- to 14-day delay in decision making. If the test is still not feasible, the pregnancy is actually at higher risk for an adverse outcome [61] and subsequent pregnancy control is recommended. …”
Section: What Can the Individual Pregnant Woman Learn From Nipt?mentioning
confidence: 99%